Assessment of Knowledge and Skills for Technology Integration among Primary School Teachers in Kano State Nigeria - Ibrahim, Tanimu Adam (IJOEM Indonesian Journal of E-learning and Multimedia, 2025)
This study aimed to assess the knowledge and skills of primary school teachers in Kano State, Nigeria, in terms of integrating technology into classroom teaching. It studied the knowledge, skills, factors influencing technology integration, and barriers faced by primary school teachers in Kano State, Nigeria. The aim was to evaluate the readiness of teachers for effective technology use in the classroom and identify key challenges to its integration. A survey design was employed, with data collected from 365 teachers using a structured questionnaire. Descriptive and inferential statistical analyses were conducted to examine the teachers' technology knowledge, skills, and perceptions of the barriers to integration. The results revealed that most teachers possessed moderate to low levels of technology knowledge and skills, with positive attitudes and access to technology being key factors influencing adoption. Major barriers included inadequate infrastructure, limited access to training, and resistance to change. The study also identified significant differences in technology knowledge based on years of teaching experience, and significant relationships between barriers and technology use. The findings highlight the need for targeted interventions, including professional development programs, improved infrastructure, and policies that promote a positive attitude toward technology. These interventions are crucial for enhancing technology integration in primary education and improving educational outcomes in Kano State.